THE ROLE OF SMALL AND MEDIUM ENTERPRISES (SME) ON THE ECONOMY - Reswita; Andi Irawan; Ketut Sukiyono (International Journal of Social Science, 2021)
SME is the productive economic activity widely occupied by the people to sustain their household economy, community, and nation's economy. The SME sector can stand firmly as one of the economic prime-movers for many circles within the community, providing and absorbing workforce to decrease unemployment in the society. The presence of SMEs can also provide added value on farming products so that the farming commodity may increase its usefulness value. This article aims to discuss the role of SMEs in the Indonesian economy. The research method implemented in arranging this study is a literature study by reviewing articles published by the previous writers and examining the abstract of those researches. Based on the literature study, this research concluded that SME presence, either internationally, nationally, or developing economic growth in various regions in Indonesia. The SME has the crucial meaning and roles for developing and increasing the income (PDB and PDRB), provider and employee/workforce, diminishing poverty rate, increasing investment rate, increasing foreign commerce through export, and contributing tax as the state income sources.